Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Section 6.2 - Factoring Trinomials of the Form x2+bx+c - Practice - Page 427: 9


(a) $4(x-3)(x-3)$ (b) $x(x-1)(x+4)$

Work Step by Step

Part (a) $4x^{2}-24x+36=$ $4(x^{2}-6x+9)=$ $4(x^{2}-3x-3x+9)=$ $4(x(x-3)-3(x-3))=$ $4(x-3)(x-3)$ Part (b) $x^{3}+3x^{2}-4x=$ $x(x^{2}+3x-4)=$ $x(x^{2}-1x+4x-4)=$ $x(x(x-1)+4(x-1))=$ $x(x-1)(x+4)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.